Concentration and purification of enteroviruses by membrane chromatography. - Henderson, M (1976)
A simple procedure for the concentration and partial purification of enteroviruses from tissue culture harvests is described. After removal of acid-precipitating components with a cationic detergent, the detergent and most membrane-coating components were removed by treatment with a cationic-exchange resin. The resin effluent was then acidified, and the virus was adsorbed to epoxy-fiberglass membranes. Virus was then eluted with pH 11.5 glycine-NaOH buffer. Since this eluate contains no orgcentrated simply by acidifying the eluate and passing it through a smaller membrane than that used for the first concentration. As high as 500-fold concentrations can be achieved, with a high efficiency of recovery.